PENGARUH INTENSITAS HUJAN DAN PENUTUP LAHAN (LAND COVER) TERHADAP NILAI KOEFISIEN ALIRAN PERMUKAAN (C) MENGGUNAKAN RAINFALL SIMULATOR - Akara, Rado; Sarino, Sarino; Yuono, Agus Lestari (CANTILEVER, 2016)
The influence of land cover and intensity is one of the factors that influence the value of surface flow coefficient (C). The coefficient value will affect the surface flow occurs during peak discharge. In this research, calculate surface coefficient (C) with variation intensity 40 mm/h, 50 mm/h, 60 mm/h, 70 mm/h for land cover paving block (brick pattern and matting pattern), grass block , mini elephant grass, sand and concrete pavement. This test is expected to be the solution in choosing the right type of land cover as a substitute for concrete pavement in the parking lot, park, or home or office yard. The implementation methodology was carried out by laboratory testing with rainfall simulator, 4 cm high base layer of sand and various land cover around 4 cm. The test that carried out in this study include filter analysis, rain intensity and surface coefficient value (C) testing. Testing value of coefficient including the test using rational formulas and testing by definition (Scwab, 1981 and Mc Guen, 1989). The result of this research obtained coefficient of land cover paving block pattern of stacking brick 0,857-0,891, in land cover paving block matting pattern 0,825-0,856, while at grass block 0,677-0,765. The coefficient of surface flow (C) for concrete pavement cover is 0.961-0,997, mini elephant grass cover is 0,483-0,538, while without land cover is 0,559-0,639. The value of surface flow coefficient (C) is getting bigger with increased rain intensity and land cover that has fewer gaps, in this case there is a significant difference in the paving block and grass block.